Il procedimento disciplinare notarile e la sua evoluzione storica - Parente, Ferdinando (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In the law of 16 February 1913, no. 89, the notarial disciplinary procedure was modified introducing diversification of powers according to the severity of the penalties. For the most serious disciplinary sanctions – fine, suspension and dismissal – the jurisdiction was assigned to the common courts, namely the Court of First Instance, the Court of Appeal and the Court of Cassation. For the less serious penalties – warnings and censorships – the jurisdiction was conferred on the District Notary Council, which rulings could be challenged in front of common courts. Dec. 1, 2006, no. 249 has radically altered the regime of the notarial disciplinary procedure and established the Regional Disciplinary Commission (Co.Re.Di.), which has an administrative nature, concerning the application of disciplinary sanctions and precautionary measures, as well as the assessment of the conditions of temporary or definitive termination of notarial functions. In the framework of the reform, however, the District Notary Council was assigned the mere task of supervision and control over the regular conduct of the notary activity and the power to initiate disciplinary proceedings through the right of action was attributed to its chairman.